2014
DOI: 10.7860/jcdr/2014/8537.4842
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Asymptomatic Bacteriuria and Associated Risk Factors Among Pregnant Women in Mangalore, Karnataka, India

Abstract: IntrOductIOnUrinary tract infections are relatively common problems during pregnancy. The physiologic changes related to pregnancy make healthy women susceptible to complications such as asymptomatic and symptomatic urinary tract infections. The combination of mechanical, hormonal and physiologic changes during pregnancy contributes to significant changes in the urinary tract, which has a profound impact on the acquisition and natural history of bacteriuria during pregnancy [1]. The purpose of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 15 publications
3
38
0
5
Order By: Relevance
“…The prevalence of ASB in the study group was 30.5% which is significantly high when compared with findings of Annie Rajaratnam et al (13.2%), Sujatha R et al (7.2%) and on par to findings of Neupane et al (26.5%) and less than findings of Imade et al (45.3%) who reported higher prevalence of ASB in their studies. [6][7][8][9] Variations among these studies may be due to differences in environmental conditions, socioeconomic statuses, social habits of the community and educational level of the patients in the study. In present study the highest prevalence was noticed in the age group of 25 -30 years with 52.46% which coincides with findings of Alghalibi et al (55.62%), Sujatha R et al, (72.72%) but some studies reported a higher prevalence in the age group of 20-25 years.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ASB in the study group was 30.5% which is significantly high when compared with findings of Annie Rajaratnam et al (13.2%), Sujatha R et al (7.2%) and on par to findings of Neupane et al (26.5%) and less than findings of Imade et al (45.3%) who reported higher prevalence of ASB in their studies. [6][7][8][9] Variations among these studies may be due to differences in environmental conditions, socioeconomic statuses, social habits of the community and educational level of the patients in the study. In present study the highest prevalence was noticed in the age group of 25 -30 years with 52.46% which coincides with findings of Alghalibi et al (55.62%), Sujatha R et al, (72.72%) but some studies reported a higher prevalence in the age group of 20-25 years.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of micro organisms can attack the urinary tract and is responsible for the pathogenesis of urinary tract infection [1][2][3][4] . These are the most common bacterial infections during pregnancy accounting to 10% of hospital visits by women 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore ASB prevalence differs from setting to setting. E. coli is the most common isolate in ASB as it was also confirmed in a prospective study in Odisha state, India and in Abuja (56.%) [19][20][21][22][23]. CoNS is one of isolated uropathogens [25].…”
Section: Discussionmentioning
confidence: 74%
“…This prevalence was above the general range of 2% to 10% but fits in the range from 1.9% to 15% being reported [20]. The prevalence in this study was close to 13.2% found in Mangalore, Karnataka in India [21]. Higher prevalence (46.6%, 46.5%) for ASB was found in Bangalor in India, Abakaliki Nigeria and lower prevalence of 12.8% in Abuja [22][23][24].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation